Aqueous carbon nanotube conductive slurry and preparation method thereof

Through preliminary detangling and emulsification of specific solvents, the aqueous dispersion of carbon nanotubes is improved, the problems of small dispersion amount and reduced conductivity are solved, and a high content and excellent conductivity are prepared for aqueous carbon nanotube conductive paste, which is suitable for a variety of high-end fields.

CN117820888BActive Publication Date: 2025-04-18JIANGNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311654070.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-04
Publication Date
2025-04-18
Estimated Expiration
2043-12-04

AI Technical Summary

Technical Problem

The dispersion method of carbon nanotubes will damage their structure to a certain extent, resulting in reduced conductivity and smaller dispersion.

Method used

A specific phenol solvent is used to initially diswrap carbon nanotubes, and the oily dispersion of carbon nanotubes is emulsified in water by dispersing agent as an emulsifier, increasing the contact area between the dispersing agent and the carbon nanotubes, and an oil-in-water emulsion is prepared. Then, the aqueous carbon nanotube mud is obtained by evaporation of solvent or centrifugation and washing with water, and finally dispersed with the thickener in water to prepare an aqueous carbon nanotube conductive paste.

Benefits of technology

The dispersion and stability of carbon nanotubes in the aqueous phase are significantly improved, so that the content of carbon nanotubes in the prepared conductive paste reaches 2%-10%, and it shows excellent conductivity and adhesion. It is suitable for electronic labels, new energy, coatings and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117820888B_ABST
    Figure CN117820888B_ABST
Patent Text Reader

Abstract

The present invention discloses an aqueous carbon nanotube conductive paste and a preparation method thereof, and belongs to the technical field of coatings. The present invention adopts a specific solvent (phenol solvent) to preliminarily disentangle carbon nanotubes, and uses the amphiphilicity of a specific dispersant combination (sodium dodecylbenzene sulfonate and polyvinyl pyrrolidone) as an emulsifier to emulsify the carbon nanotube oil dispersion in water, increase the contact area between the dispersant and the carbon nanotubes, and obtain an oil-in-water emulsion; then demulsify to obtain an aqueous carbon nanotube mud; finally, the aqueous carbon nanotube mud and a thickener are dispersed in water to prepare an aqueous carbon nanotube conductive paste. The present invention can disperse a higher concentration of carbon nanotubes so that the content of carbon nanotubes in the prepared conductive paste is 2%-10%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a water-based carbon nanotube conductive slurry and a preparation method thereof, belonging to the technical field of coatings. Background Art

[0002] Conductive paste refers to a paste formed by uniformly dispersing conductive fillers in water, organic solvents, and resin systems. Water-based conductive paste is a functional paste that has both the characteristics of water-based paste and conductive ability. Due to its safety, environmental protection, and low toxicity, it has become an important material in advanced high-end fields such as advanced micro-nano manufacturing, printed electronics, and biomedicine.

[0003] Aqueous conductive slurry is generally composed of conductive filler, dispersant, thickener and solvent. Commonly used conductive fillers are mainly conductive carbon materials, including carbon nanotubes, graphene oxide, graphite, etc. Conventional conductive carbon materials have the advantages of many types, low cost and stable performance. Among them, carbon nanotubes have a large specific surface area, strong van der Waals force between particles, and are very easy to agglomerate in water, so how to achieve effective dispersion of carbon nanotubes has become a key issue that needs to be solved urgently.

[0004] At present, in order to improve the water dispersibility of carbon nanotubes, the two commonly used methods are covalent chemical modification and non-covalent chemical modification. Among them, covalent chemical modification is to use strong oxidizing acids to oxidize carbon nanotubes, so that carbon nanotubes have functional groups such as carboxyl or hydroxyl groups, which can effectively improve the dispersibility of carbon nanotubes; but it will destroy its structure and easily cause great harm to the environment. Non-covalent chemical modification is to add surfactants to disperse carbon nanotubes, which can give play to the excellent physical and chemical advantages of carbon nanotubes; however, the use of surfactants often requires long-term ultrasound, which destroys the structure of carbon nanotubes to a certain extent, and the dispersion amount of carbon nanotubes is very small, so that the solid content of carbon nanotubes in the prepared slurry is very small, generally less than 2%. Summary of the invention

[0005] [Technical issues]

[0006] The dispersion method of carbon nanotubes will destroy the structure of carbon nanotubes to a certain extent, resulting in reduced conductivity; and the dispersion amount of carbon nanotubes is very small.

[0007] [Technical solution]

[0008] In order to solve the above problems, the present invention provides a method for dispersing carbon nanotubes in a low power and short time under the condition of using a surfactant. The present invention uses a specific solvent (phenol solvent) to preliminarily disentangle the carbon nanotubes, and uses a dispersant as an emulsifier to emulsify the carbon nanotube oil dispersion in water, increase the contact area between the dispersant and the carbon nanotubes, and obtain an oil-in-water emulsion; then the solvent is evaporated or centrifuged and washed to obtain an aqueous carbon nanotube mud; finally, the aqueous carbon nanotube mud and the thickener are dispersed in water to prepare an aqueous carbon nanotube conductive slurry. The present invention can disperse a higher concentration of carbon nanotubes so that the content of carbon nanotubes in the prepared conductive slurry is 2%-10%. The conductive slurry prepared by the present invention has good application prospects in the fields of electronic tags, new energy, coatings, inks, batteries, artificial intelligence, aerospace, communications, plastics, fibers, fabrics, etc.

[0009] The first object of the present invention is to provide a method for preparing an oil-in-water emulsion based on carbon nanotubes, comprising the following steps:

[0010] (1) Oil phase:

[0011] Ultrasonic dispersion of carbon nanotubes in a solvent to obtain a carbon nanotube dispersion; wherein the solvent is a single phenol solvent or a mixed solvent of a phenol solvent and a low dielectric constant solvent;

[0012] (2) Water phase:

[0013] Dispersing a dispersant in water to obtain a dispersant aqueous solution; wherein the dispersant is one or more dispersants selected from the group consisting of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, polyvinyl pyrrolidone, sodium deoxycholate, graphene oxide, and the like;

[0014] (3) Preparation of oil-in-water emulsion:

[0015] The carbon nanotube dispersion is added dropwise into the dispersant aqueous solution for emulsification to obtain an oil-in-water emulsion based on carbon nanotubes.

[0016] In one embodiment of the present invention, in step (1), the average diameter of the carbon nanotubes is 7-11 nm, and the length of the carbon nanotubes is 5-20 μm.

[0017] In one embodiment of the present invention, the concentration of the carbon nanotube dispersion in step (1) is 5-10 mg / mL.

[0018] In one embodiment of the present invention, the ultrasonic dispersion in step (1) is water bath ultrasonic dispersion, specifically, ultrasonic and stirring treatment at 40-50W, 300-500rpm, 20-30°C for 5-15min.

[0019] In one embodiment of the present invention, the phenol solvent in step (1) is any one or more of m-cresol, o-cresol, p-cresol, and resorcinol; the low dielectric constant solvent is one or more of n-hexane, 1,4-dioxane, toluene, anisole, and chloroform.

[0020] In one embodiment of the present invention, the mass ratio of the phenol solvent to the low dielectric constant solvent in the mixed solvent of the phenol solvent and the low dielectric constant solvent in step (1) is 3-5:1.

[0021] In one embodiment of the present invention, in step (2), the dispersant is sodium dodecyl sulfate (SDS) and polyvinyl pyrrolidone (PVP), and the mass ratio of the two is 1:1-4; the dispersant is sodium dodecylbenzene sulfonate (SDBS) and polyvinyl pyrrolidone (PVP), and the mass ratio of the two is 1:1-4.

[0022] In one embodiment of the present invention, the dispersion in step (2) is a stirring dispersion, specifically, stirring at 20-30° C. (normal temperature) and 300-500 rpm for 5-15 min.

[0023] In one embodiment of the present invention, the mass ratio of the carbon nanotubes in step (1) to the dispersant in step (2) is 1:1-10.

[0024] In one embodiment of the present invention, the dropwise addition rate in step (3) is 8-10 mL / min.

[0025] In one embodiment of the present invention, the emulsification in step (3) is carried out at 20-30° C. and 600-1000 rpm for 20-40 min.

[0026] The second object of the present invention is the carbon nanotube-based oil-in-water emulsion prepared by the method of the present invention.

[0027] The third object of the present invention is to provide a method for preparing water-based carbon nanotube slurry, comprising the following steps:

[0028] The water-in-oil emulsion based on carbon nanotubes is subjected to solvent evaporation or centrifugal washing to obtain water-based carbon nanotube slurry.

[0029] In one embodiment of the present invention, the centrifugal water washing is performed at 10000 rpm-11000 rpm for 10-20 min; the number of centrifugation is 1-5 times, so that the solid content is 20-30%.

[0030] The fourth object of the present invention is the aqueous carbon nanotube slurry prepared by the method described in the present invention.

[0031] A fifth object of the present invention is to provide a method for preparing an aqueous carbon nanotube conductive slurry, comprising the following steps:

[0032] Water, aqueous carbon nanotube slurry and thickener solution are mixed, stirred and ultrasonicated to obtain aqueous carbon nanotube conductive slurry.

[0033] In one embodiment of the present invention, the thickener is one or more of sodium carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), polyurethane, and sodium polyacrylate, and the mass concentration of the thickener solution is 5-15%.

[0034] In one embodiment of the present invention, the mass ratio of water, aqueous carbon nanotube slurry and thickener solution is 1:0.5-2:0.1-1.

[0035] In one embodiment of the present invention, the stirring is carried out at 20-30° C. and 600-1000 rpm for 20-40 min.

[0036] In one embodiment of the present invention, the ultrasound is performed at 20-30° C. and 40-50 W for 20-40 min.

[0037] The sixth objective of the present invention is the aqueous carbon nanotube conductive slurry prepared by the method of the present invention.

[0038] In one embodiment of the present invention, the solid content of the aqueous carbon nanotube conductive slurry is 5%-15%.

[0039] A seventh object of the present invention is to provide a method for preparing a water-based carbon nanotube conductive coating, comprising the following steps:

[0040] Applying water-based carbon nanotube conductive slurry on the surface of the substrate and drying it to obtain a conductive coating;

[0041] Wherein, the substrate is PET film, PI film or glass;

[0042] Drying is done at 50-60°C for 0.5-1.5h;

[0043] The thickness of the conductive coating is 5-50 μm.

[0044] The eighth objective of the present invention is the application of the carbon nanotube-based oil-in-water emulsion, aqueous carbon nanotube slurry, and aqueous carbon nanotube conductive slurry described in the present invention in the fields of electronic tags, new energy, coatings, inks, batteries, artificial intelligence, aerospace, communications, plastics, fibers or fabrics.

[0045] A ninth object of the present invention is to provide a method for improving the dispersion performance of high-concentration carbon nanotubes in an aqueous solution, comprising the following steps:

[0046] (1) Oil phase:

[0047] Ultrasonic dispersion of carbon nanotubes in a solvent to obtain a carbon nanotube dispersion; wherein the solvent is a single phenol solvent or a mixed solvent of a phenol solvent and a low dielectric constant solvent;

[0048] (2) Water phase:

[0049] Dispersing a dispersant in water to obtain a dispersant aqueous solution; wherein the dispersant is one or more dispersants selected from the group consisting of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, polyvinyl pyrrolidone, sodium deoxycholate, graphene oxide, and the like;

[0050] (3) Preparation of oil-in-water emulsion:

[0051] The carbon nanotube dispersion is added dropwise into the dispersant aqueous solution for emulsification to obtain an oil-in-water emulsion based on carbon nanotubes.

[0052] [Beneficial Effects]

[0053] (1) The present invention uses a specific solvent to disperse carbon nanotubes, which greatly reduces the time and power of ultrasound, avoids destroying the structure of the carbon nanotubes themselves and weakening the performance of the carbon nanotubes, and makes the water-based carbon nanotube conductive slurry show excellent conductivity.

[0054] (2) The present invention prepares a highly dispersed aqueous carbon nanotube conductive paste through an emulsification process, significantly improves the dispersibility and stability of carbon nanotubes in the aqueous phase, and determines the optimal process for preparing the aqueous carbon nanotube conductive paste.

[0055] (3) The present invention uses a specific solvent to preliminarily disentangle the carbon nanotubes, which greatly improves the dispersion effect of the carbon nanotubes compared to direct dispersion by adding a dispersant in water, and has good dispersibility at a higher carbon nanotube content.

[0056] (4) The carbon nanotube slurry prepared by the present invention has good water dispersibility and good compatibility with water-based resins, and can be compounded with water-based resins to prepare stable water-based slurry.

[0057] (5) The aqueous carbon nanotube conductive slurry prepared by the present invention uses deionized water as the dispersion medium, thereby reducing pollution to the environment.

[0058] (6) The aqueous carbon nanotube conductive slurry prepared by the present invention exhibits excellent conductivity and adhesion, and the slurry has good stability and can be stably stored for more than 2 months; it has broad application prospects in the fields of electronic tags, new energy, coatings, inks, batteries, artificial intelligence, aerospace, communications, plastics, fibers, fabrics, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is a physical photo of the aqueous carbon nanotube conductive paste in Example 9.

[0060] Figure 2 This is a physical photo of the aqueous carbon nanotube conductive paste in Example 9.

[0061] Figure 3 This is the particle size distribution diagram of the aqueous carbon nanotube conductive slurry prepared in Example 9.

[0062] Figure 4 This is the particle size distribution diagram of the conductive paste prepared in Comparative Example 6.

[0063] Figure 5 TEM images of the aqueous carbon nanotube conductive slurry prepared in Example 9 and Comparative Example 6; wherein A is the slurry of Example 9, with a magnification of 40,000; B is the slurry of Example 9, with a magnification of 40,000; C is the slurry of Comparative Example 6, with a magnification of 40,000; and D is the slurry of Comparative Example 6, with a magnification of 40,000. DETAILED DESCRIPTION

[0064] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0065] Test method:

[0066] 1. Particle size distribution test:

[0067] The zeta potential and nanoparticle size analyzer (NanoBrook Omni) produced by Brookhaven was used to test the particle size distribution of the aqueous highly dispersed carbon nanotube conductive slurry.

[0068] 2. Stability test:

[0069] Let the aqueous highly dispersed carbon nanotube conductive slurry stand for a week and observe whether there is precipitation at the bottom; if there is precipitation, observe whether it can be dispersed again after shaking.

[0070] 3. Dispersion test:

[0071] Take 2 drops of aqueous carbon nanotube conductive slurry and drop them into 50 mL of deionized water. Ultrasonicate at 25°C and 45W for 1 min. If there are no particles visible to the naked eye, the dispersion is good; the dispersion is good after 2 minutes; the dispersion is poor after more than 2 minutes.

[0072] 4. Resistance:

[0073] Use a multimeter to test.

[0074] The raw materials used in the embodiments and comparative examples are:

[0075] Multi-walled carbon nanotubes: average diameter 7-11 nm, carbon tube length 5-20 μm, purchased from Jiangsu Tiannai Technology Co., Ltd. (FT7320 CNT);

[0076] In the examples, reactions without specific reference to reaction temperature were carried out at room temperature (25° C.).

[0077] Example 1

[0078] A method for preparing an oil-in-water emulsion based on carbon nanotubes comprises the following steps:

[0079] (1) Oil phase:

[0080] 0.15 g of carbon nanotubes were added to 30 g of m-cresol, and the mixture was treated with ultrasonic stirring at 45 W, 400 rpm, and 25° C. for 10 min to obtain a carbon nanotube dispersion.

[0081] (2) Water phase:

[0082] 0.2 g sodium dodecyl sulfate (SDS) and 0.4 g polyvinyl pyrrolidone (PVP) were dispersed in 120 g water at 25° C. (normal temperature) with stirring (400 rpm) for 5 min to obtain a dispersant aqueous solution;

[0083] (3) Preparation of oil-in-water emulsion:

[0084] The carbon nanotube dispersion was added dropwise (5 mL / min) to the dispersant aqueous solution, and emulsified at 25° C. (normal temperature) and 800 rpm for 30 min to obtain an oil-in-water emulsion based on carbon nanotubes.

[0085] Example 2

[0086] Adjust step (2) of Example 1 to:

[0087] 0.3 g of sodium dodecyl sulfate (SDS) and 0.3 g of polyvinyl pyrrolidone (PVP) were dispersed in water at 25° C. (normal temperature) with stirring (400 rpm) to obtain a dispersant aqueous solution;

[0088] The rest was consistent with Example 1 to obtain an oil-in-water emulsion based on carbon nanotubes.

[0089] Example 3

[0090] Adjust step (2) of Example 1 to:

[0091] 0.15 g of sodium dodecyl sulfate (SDS) and 0.45 g of polyvinyl pyrrolidone (PVP) were dispersed in water at 25° C. (normal temperature) with stirring (400 rpm) to obtain a dispersant aqueous solution;

[0092] The rest was consistent with Example 1 to obtain an oil-in-water emulsion based on carbon nanotubes.

[0093] Example 4

[0094] Adjust step (1) of Example 1 to:

[0095] 0.15 g of multi-walled carbon nanotubes was added to 30 g of a mixed solvent of m-cresol and 1,4-dioxane (the mass ratio of m-cresol to 1,4-dioxane was 4:1), and the mixture was subjected to ultrasonic stirring at 45 W, 400 rpm, and 25° C. for 10 min to obtain a carbon nanotube dispersion.

[0096] The rest was consistent with Example 1 to obtain an oil-in-water emulsion based on carbon nanotubes.

[0097] Comparative Example 1

[0098] Adjust step (2) of Example 1 to:

[0099] 0.6 g of polyvinyl pyrrolidone (PVP) was dispersed in water at 25°C (normal temperature) with stirring (400 rpm) to obtain a dispersant aqueous solution;

[0100] The rest was consistent with Example 1 to obtain an oil-in-water emulsion based on carbon nanotubes.

[0101] Comparative Example 2

[0102] Adjust step (2) of Example 1 to:

[0103] 0.6 g of sodium dodecylbenzene sulfonate (SDBS) was dispersed in water at 25°C (normal temperature) with stirring (400 rpm) to obtain a dispersant aqueous solution;

[0104] The rest was consistent with Example 1 to obtain an oil-in-water emulsion based on carbon nanotubes.

[0105] Comparative Example 3

[0106] Adjust step (2) of Example 1 to:

[0107] 0.6 g of sodium dodecyl sulfate (SDS) was dispersed in water at 25°C (normal temperature) with stirring (400 rpm) to obtain a dispersant aqueous solution;

[0108] The rest was consistent with Example 1 to obtain an oil-in-water emulsion based on carbon nanotubes.

[0109] Comparative Example 4

[0110] Adjust step (2) of Example 1 to:

[0111] 0.3 g of sodium dodecylbenzene sulfonate (SDBS) and 0.3 g of polyvinyl pyrrolidone (PVP) were dispersed in water at 25° C. (normal temperature) with stirring (400 rpm) to obtain a dispersant aqueous solution;

[0112] The rest was consistent with Example 1 to obtain an oil-in-water emulsion based on carbon nanotubes.

[0113] Comparative Example 5

[0114] Adjust Example 1 to:

[0115] 0.15 g of carbon nanotubes, 0.2 g of sodium dodecyl sulfate (SDS) and 0.4 g of polyvinyl pyrrolidone (PVP) were added to 15 g of water, and the mixture was treated with ultrasonic stirring at 45 W, 400 rpm and 25° C. for 4 h to obtain a carbon nanotube dispersion.

[0116] Example 5

[0117] A method for preparing water-based carbon nanotube slurry comprises the following steps:

[0118] The carbon nanotube-based oil-in-water emulsion of Example 1 was ultrasonicated for 10 minutes at 25°C (normal temperature) and 60W power using a cell crusher; then it was centrifuged and washed with water at 10,000 rpm for 15 minutes, and the centrifugal washing was repeated 3 times to obtain an aqueous carbon nanotube sludge with a solid content of 20%.

[0119] Example 6

[0120] A method for preparing water-based carbon nanotube slurry comprises the following steps:

[0121] The carbon nanotube-based oil-in-water emulsions of Examples 2-4, the carbon nanotube-based oil-in-water emulsions of Comparative Examples 1-4, and the carbon nanotube dispersion prepared in Comparative Example 5 were ultrasonicated for 10 minutes at 25°C (normal temperature) and a power of 60 W using a cell crusher; then they were centrifuged and washed with water at 10,000 rpm for 15 minutes, and the centrifugal washing was repeated 3 times to obtain an aqueous carbon nanotube sludge with a solid content of 20%.

[0122] Example 7

[0123] A method for preparing an aqueous carbon nanotube conductive slurry comprises the following steps:

[0124] 3 g of the aqueous carbon nanotube slurry of Example 5 was mixed with 3 g of water and 0.6 g of a 10% PVA aqueous solution, stirred at 800 rpm for 30 min at 25° C. (room temperature), and ultrasonicated at 45 W for 30 min at 25° C. (room temperature) to obtain an aqueous carbon nanotube conductive slurry.

[0125] Example 8

[0126] A method for preparing an aqueous carbon nanotube conductive slurry comprises the following steps:

[0127] 3 g of the aqueous carbon nanotube slurry of Example 6 was mixed with 3 g of water and 0.6 g of a 10% PVA aqueous solution, stirred at 25°C (room temperature) and 800 rpm for 30 min, and ultrasonicated at 25°C (room temperature) and 45W for 30 min to obtain an aqueous highly dispersed carbon nanotube conductive slurry.

[0128] The performance of the aqueous highly dispersed carbon nanotube conductive slurry obtained in Examples 5-8 was tested, and the test results are as follows:

[0129] Table 1

[0130]

[0131]

[0132] Example 9

[0133] A method for preparing an aqueous carbon nanotube conductive slurry comprises the following steps:

[0134] 3 g of the aqueous carbon nanotube slurry of Example 5 was mixed with 3 g of water and 0.6 g of a 10% sodium carboxymethyl cellulose aqueous solution, stirred at 800 rpm for 30 min at 25° C. (room temperature), and ultrasonicated at 45 W for 30 min at 25° C. (room temperature) to obtain an aqueous highly dispersed carbon nanotube conductive slurry.

[0135] Example 10

[0136] A method for preparing an aqueous carbon nanotube conductive slurry comprises the following steps:

[0137] The carbon nanotube-based oil-in-water emulsion in Example 1 was ultrasonically cleaned at 25° C. (normal temperature) and 45 W for 30 min using an ultrasonic cleaner; then centrifuged and washed at 10,000 rpm for 15 min, and the centrifugal washing was repeated 3 times to obtain an aqueous carbon nanotube slurry with a solid content of 20%;

[0138] 3 g of water, 3 g of aqueous carbon nanotube slurry and 0.6 g of 10% carboxymethyl cellulose aqueous solution were mixed, stirred at 800 rpm for 30 min at 25° C. (room temperature), and ultrasonicated at 45 W for 30 min at 25° C. (room temperature) to obtain aqueous carbon nanotube conductive slurry.

[0139] Comparative Example 6

[0140] The sodium carboxymethyl cellulose in Example 9 was omitted, and the other parts were kept the same as in Example 9 to obtain a conductive paste.

[0141] Comparative Example 7

[0142] The amount of water in step (2) of Example 1 was adjusted to 270 g, and the other contents were kept consistent with Examples 1, 5, and 7 to prepare a conductive paste.

[0143] Comparative Example 8

[0144] The amount of water in step (2) of Example 1 was adjusted to 270 g, and the other contents were kept the same as in Example 1 to obtain an oil-in-water emulsion; and then a conductive paste was prepared according to Example 9.

[0145] Embodiment 11

[0146] A method for preparing a water-based carbon nanotube conductive coating comprises the following steps:

[0147] The conductive pastes prepared in Examples 9 and 10 and Comparative Examples 7-8 were coated on a PET film with a coating thickness of 40 μm using a 1000 μm scraper, and dried in an oven at 60° C. for 60 min to prepare a conductive coating.

[0148] The prepared conductive coating was subjected to performance tests, and the test results are as follows:

[0149] Table 2

[0150] example Particle size (nm) Resistance (Ω) Dispersibility stability Example 9 364.9 120 better No precipitation Example 10 294.9 60 good No precipitation Comparative Example 6 282.4 80 better There is precipitation, which can be dispersed after shaking Comparative Example 7 268.2 100 better There is precipitation, which can be dispersed after shaking Comparative Example 8 258.2 45 good No precipitation

[0151] Figure 3 This is the particle size distribution diagram of the aqueous carbon nanotube conductive slurry prepared in Example 9. Figure 4 This is the particle size distribution diagram of the conductive paste prepared in Comparative Example 6. Figure 3 and Figure 4 It can be seen from the comparison that the particle size is smaller and the distribution is narrower after adding CMC, which shows that adding CMC can effectively prevent the agglomeration of carbon nanotubes.

[0152] Figure 5 The transmission electron microscope images of the aqueous carbon nanotube conductive paste prepared in Example 9 and Comparative Example 6 are shown in Figure 1. A is the paste of Example 9, with a magnification of 4000; B is the paste of Example 9, with a magnification of 40000; C is the paste of Comparative Example 6, with a magnification of 40000; and D is the paste of Comparative Example 6, with a magnification of 40000. Figure 5 It can be seen that the carbon nanotubes prepared in Example 1 are basically not entangled together and are well dispersed; the lengths are basically between 1-2 μm, and there are no individual short ones, which can indicate that the preparation process of the present invention has basically no damage to the carbon nanotubes.

[0153] Example 12

[0154] The parameters of the cell crusher in Example 5 were adjusted as shown in Table 3, and the other parameters were kept consistent with Example 5. The aqueous carbon nanotube slurry was then prepared according to Example 7 to obtain a conductive slurry.

[0155] The obtained conductive paste was subjected to performance testing, and the test results are as follows:

[0156] Table 3

[0157]

[0158]

[0159] Example 13

[0160] The power and time of the ultrasonic cleaner in Example 10 were adjusted as shown in Table 4, and the rest were kept the same as in Example 10 to obtain a conductive slurry.

[0161] The obtained conductive paste was subjected to performance testing, and the test results are as follows:

[0162] Table 4

[0163]

[0164] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing an oil-in-water emulsion based on carbon nanotubes, characterized in that: The steps include: (1) Oil phase: ultrasonically dispersing the carbon nanotubes in a solvent to obtain a carbon nanotube dispersion; The solvent is a single phenol solvent or a mixed solvent of a phenol solvent and a low dielectric constant solvent; the phenol solvent is any one or more of m-cresol, o-cresol, p-cresol, and resorcinol; the low dielectric constant solvent is one or more of n-hexane, 1,4-dioxane, toluene, anisole, and chloroform; (2) Water phase: Dispersing a certain amount of dispersant in water to obtain a dispersant aqueous solution; The dispersant is sodium dodecyl sulfate and polyvinyl pyrrolidone, and the mass ratio of the two is 1:1-3; (3) Preparation of oil-in-water emulsion: The carbon nanotube dispersion is added dropwise into the dispersant aqueous solution for emulsification to obtain an oil-in-water emulsion based on carbon nanotubes.

2. The carbon nanotube-based oil-in-water emulsion prepared by the method according to claim 1.

3. A method for preparing water-based carbon nanotube slurry, characterized in that: The steps include: The carbon nanotube-based oil-in-water emulsion according to claim 2 is subjected to solvent evaporation or centrifugal water washing to obtain an aqueous carbon nanotube slurry.

4. The aqueous carbon nanotube slurry prepared by the method according to claim 3.

5. A method for preparing an aqueous carbon nanotube conductive slurry, characterized in that: The steps include: Mixing water, the aqueous carbon nanotube slurry according to claim 4 and a thickener solution, stirring and ultrasonicating to obtain an aqueous carbon nanotube conductive slurry; The ultrasound was carried out at 25°C and 45W for 30 min.

6. Aqueous carbon nanotube conductive slurry prepared by the method according to claim 5.

7. A method for preparing a water-based carbon nanotube conductive coating, characterized in that: The steps include: The aqueous highly dispersed carbon nanotube conductive slurry according to claim 6 is applied on the surface of the substrate and dried to obtain a conductive coating.

8. The water-based carbon nanotube conductive coating prepared by the method according to claim 7.

9. A method for improving the dispersion performance of high-concentration carbon nanotubes in an aqueous solution, characterized in that: The steps include: (1) Oil phase: ultrasonically dispersing the carbon nanotubes in a solvent to obtain a carbon nanotube dispersion; The solvent is a single phenol solvent or a mixed solvent of a phenol solvent and a low dielectric constant solvent; the phenol solvent is any one or more of m-cresol, o-cresol, p-cresol, and resorcinol; the low dielectric constant solvent is one or more of n-hexane, 1,4-dioxane, toluene, anisole, and chloroform; (2) Water phase: dispersing a dispersant in water to obtain a dispersant aqueous solution; The dispersant is sodium dodecyl sulfate and polyvinyl pyrrolidone, and the mass ratio of the two is 1:1-3; (3) Preparation of oil-in-water emulsion: The carbon nanotube dispersion is added dropwise into the dispersant aqueous solution for emulsification to obtain an oil-in-water emulsion based on carbon nanotubes.

Citation Information

Patent Citations

  • Dispersing method for nano material

    CN108467025A

  • Conductive slurry and preparation thereof, silicon-containing negative electrode slurry and preparation thereof, and silicon-containing negative electrode

    CN116137327A